Traditions And Religious Relations: Perceptions Of Religious Group In Kerinci, Jambi - Wahyuni, Tela; Arafik, Valezza Juliani (Contemporary Society and Politics Journal, 2022)
Indonesia has many kinds of traditions. Each region in Indonesia has different habits, characteristics, and uniqueness, as well as the practices belonging to Kerinci Regency, Jambi Province, namely "Kenduri Sko," a hereditary tradition. From ancestral heritage. Various series of trades are carried out in the Kenduri Sko tradition, namely in the form of inauguration or inauguration of traditionary positions on depati, ninik mamak, hulubalang, and traditional stakeholders, lowering and purifying sko (heritage objects) using lime juice, balimau bath for all people and guests who are present are allowed to participate, then ends with a large keduri in the area. The community in Kerinci is a society whose majority adheres to Islam and has several religious groups spread across the Kerinci area. Of course, each of these religious groups has its perception of adat, which the Kerinci people always uphold. This research intends to determine the perceptions of each religious group in Kerinci regarding this Kenduri Sko tradition, how the forms of religious values ​​contained in the Kenduri Sko tradition according to religious groups, and how harmony, harmony, and inequality exist in culture and religion in Kerinci. The research method was carried out by directly interviewing each known religious group and conducting a literature study. The research results are that every religious group in Kerinci has the same opinion, and there are also differences. Of course, each religious group has its perception of Tradition, which is always upheld by the Kerinci community. This research intends to determine the perceptions of each religious group in Kerinci regarding this Kenduri Sko tradition, how the forms of religious values ​​contained in the Kenduri Sko tradition according to religious groups, and how harmony, harmony, and inequality exist in culture and religion in Kerinci.